The Obligation of Hijab in the Perspective of Maqasidi Interpretation: A Critical Study of Gender Equality Perspectives: فريضة الحجاب من منظور التفسير المقاصدي: دراسة نقدية لوجهة نظر المساواة بين الجنسين - Ramadhan, Abdul Rahman; Farabi, Muhammad Nadzif Zaky El; Zain, Bayu Rizky Fachri; Nugroho, Kevin Zidane; Kurniawan, Nabil Rasheed; Alkhalidi, Aminullah (ZAD Al-Mufassirin, 2025)
The debate over the hijab obligation for Muslim women has long been a pivotal issue in religious and social discussions. The hijab requirement is often seen as a gender restriction and is sometimes rejected in the context of gender equality. This study aims to examine the wisdom behind the hijab obligation from a maqasid sharia perspective, while critiquing common misconceptions related to gender equality. This qualitative research utilizes secondary data, gathered through literature reviews from books, journals, and scientific articles related to Qur'anic interpretation and maqasid sharia. Content analysis is employed to explore the meanings and wisdom of the hijab obligation. The results show that the hijab is not merely a religious command but also encompasses profound social and spiritual purposes. The study concludes that a maqasid sharia approach provides a broader understanding of the hijab’s function, portraying it as a form of protection and respect for Muslim women..